The Business Law and Realist Legal Theory: The Practical Impact of Islamic Legal Philosophy on Economic Practice - Mahaputra, I Gede Made Agus; Darma, I Made Wirya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The convergence of legal realist theory and Islamic legal philosophy offers opportunities to harmonize substantive justice principles with ethical values in modern business law, addressing the challenges of globalization and the complexity of contemporary economic practices. This study aims to analyze the application of legal realist theory and Islamic legal philosophy in modern business law practices. It employs normative legal methods with a conceptual approach, examining the application of legal realist theory and Islamic legal philosophy in modern business law through the analysis of primary, secondary, and tertiary legal materials, as well as descriptive and normative analytical techniques to produce comprehensive practical recommendations. The findings reveal that the application of legal realist theory in value-based Islamic business law emphasizes adaptation to social realities while upholding Sharia principles such as justice, transparency, and balance, implemented in Islamic financial systems through contracts like mudharabah and murabahah. This is regulated under laws such as Law No. 21 of 2008 and supported by DSN-MUI fatwas. Furthermore, Islamic legal philosophy significantly impacts modern economic practices by integrating principles of justice and sustainability through wealth redistribution using zakat, waqf, and infaq, and promoting green economics based on the concept of al-‘imarah. With its ethics-based and socially responsible approach, Islamic legal philosophy supports long-term economic stability and the relevance of business law in a global context.